Isatuximab Plus Carfilzomib and Dexamethasone Versus Carfilzomib and Dexamethasone in Relapsed Multiple Myeloma Patients with Renal Impairment: IKEMA Subgroup Analysis - Capra, Marcelo; Martin, Thomas; Moreau, Philippe; Baker, Ross; Pour, Ludek; Min, Chang-Ki; Dimopoulos, Meletios (Ferrata Storti Foundation, 2022)
Renal impairment (RI) is common in patients with multiple myeloma (MM) and new therapies that can improve renal function are needed. The phase III IKEMA study (clinicaltrials gov. Identifier: NCT03275285) investigated isatuximab (Isa) with carfilzomib and dexamethasone (Kd) versus Kd in relapsed MM. This subgroup analysis examined results from patients with RI, defined as estimated glomerular filtration rate <60 mL/min/1.73 m(2). Addition of Isa prolonged progression-free survival (PFS) in patients with RI (hazard ratio: 0.27; 95% confidence interval [CI]: 0.11-0.66; median PFS not reached for Isa-Kd versus 13.4 months for Kd [20.8-month follow-up]). Complete renal responses occurred more frequently with Isa-Kd (52.0%) versus Kd (30.8%) and were durable in 32.0% versus 7.7% of patients, respectively. Treatment exposure was longer with Isa-Kd, with median number of started cycles and median duration of exposure of 20 versus 9 cycles and 81.0 versus 35.7 weeks for Isa-Kd versus Kd, respectively. Among patients with RI, the incidence of patients with grade >= 3 treatment-emergent adverse events was similar between the two arms (79.1% in Isa-Kd vs. 77.8% in Kd). In summary, the addition of Isa to Kd improved clinical outcomes with a manageable safety profile in patients with RI, consistent with the benefit observed in the overall IKEMA study population.
Mohty, Mohamad/0000-0002-7264-808X; Moreau, Philippe/0000-0003-1780-8746; Baker, Ross/0000-0002-2728-6788;